Hand–Schuller–Christian disease presenting with a classical triad and oral manifestations: A rare case report (Indian Journal of Case Reports, 2020)
Hand–Schuller–Christian disease is a multifocal disease that characteristically involves the bone and extraskeletal involvement of the reticuloendothelial system. The most common age group affected is children between 1 and 5 years old. It is a disseminated form of Langerhans cell histiocytosis with a typical triad of exophthalmos, diabetes insipidus, and lytic bone lesions, although seen in only half of the patients. We present such an uncommon case presenting with the classical triad along with oral manifestation such as floating teeth and hepatitis with typical radiological findings.